The burden of type 2 diabetes attributable to air pollution across China and its provinces, 1990–2021: an analysis for the Global Burden of Disease Study 2021Research in context - Chunnan Li; Jinlei Qi; Peng Yin; Xinhui Yu; Haoran Sun; Maigeng Zhou; Wannian Liang (The Lancet Regional Health. Western Pacific)
Summary: Background: Temporal trends and geographical disparities in type 2 diabetes burden attributable to air pollution, including ambient and household, are not fully understood within China. This study aims to estimate the burden of type 2 diabetes attributable to air pollution at national and provincial levels from 1990 to 2021. Methods: We assessed air pollution exposure across 33 Chinese provinces, autonomous regions, municipalities, and special administrative regions, focusing on two common forms of air pollution: ambient particulate matter pollution (defined as the annual gridded concentration of PM2.5) and household air pollution (defined as the percentage of households using solid cooking fuels and their corresponding exposure to PM2.5). We employed the methods from the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) 2021 to estimate the attribution of air pollution on type 2 diabetes deaths and disability-adjusted life years (DALYs) by age, sex, year, and province. Findings: In 2021, about a fifth of the national type 2 diabetes burden was attributable to air pollution, with an age-standardised estimate of 1.76 deaths and 110.79 DALYs per 100,000 population, higher in males. Ambient PM2.5 contributed to 16.89% of deaths and 16.36% of DALYs, while household air pollution contributed to 3.24% of deaths and 3.07% of DALYs. From 1990 to 2021, type 2 diabetes mortality rates due to ambient PM2.5 pollution increased by 264.23%, whereas those from household air pollution decreased by 80.8%. In 2021, Beijing had the highest population attributable fraction (PAFs) of DALYs due to ambient PM2.5 pollution at 19.63%, while Tibet had the highest PAFs for household air pollution at 13.72%. The age-standardised DALYs rates for type 2 diabetes due to ambient PM2.5 varied widely across provinces, from 143.8 per 100,000 people in Tianjin to 21.6 per 100,000 people in Tibet. Interpretation: Air pollution, especially ambient PM2.5, is a significant risk factor for type 2 diabetes in China. Urgent action is needed to enhance air pollution control and develop locally adapted preventive strategies to reduce the burden of air pollution-related type 2 diabetes. Funding: Sanming Project of Medicine in Shenzhen (NO. SZSM202111001).